Project management as a development tool for businesses - L.А. (Економіка, управління та адміністрування)
The article substantiates the role of project management in ensuring business development. The purpose of the article is to consider individual aspects of business development project management. The mistakes of entrepreneurs in this process have been studied. Practical recommendations for correcting these errors are formulated in the article. The task of studying the process of organizing business development by Ukrainian entrepreneurs was the purpose of the study. The research used the following methods: observation of the work of entrepreneurs and consumer behavior; analysis of economic factors of the external environment; formalization of the structure of the process under study, formulation of the research concept. Business work is divided into ongoing processes and development. Each of these activities has different goals. Therefore, the method of managing them should be different. The business development task should be singled out as a separate project. It is necessary to apply the methodology of project management to it. Taking the wrong approach slows down or closes the business. This situation was shown by statistical data. Studying your target audience and calculating the prospective business plan are a mandatory component of the preparation of a business development project. When making business decisions, entrepreneurs should use the study and analysis of information. Intuition is not always a good tool. The model of bureaucratic business and project management should no longer be applied. At the same time, the «meritocratic» leadership model and holocracy show significantly better governance outcomes. There are many project management methodologies. The entrepreneur should use the business development project management model that leads to the goal. To facilitate the process of managing large projects, it is advisable to use specialized software products.